(3GdJCUjd GdYdej hGdJWHjb GdYedjs - (3YGWa LGHQ Wg(B, (3YHO GdQMjes ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2003)
(3GdebOeGJ GdefWbjI dOQGSGJ GdLOhi(B- (3OQGSGJ GdLOhi GdHjGfjI(B- (3OQGSGJ GdLOhi GdJShjbjI(B- (3OQGSGJ GdLOhi GdafjI hGdgfOSjI(B- (3GdJbjje GdeGdj ddeTQhYGJ GdESJKeGQjI(B- (3GdLOhi GdeGdjI(B- (3GdJbjje GdEbJUGOj ddeTQhY aj EWGQ GdXQha GdEbJUGOjI(B- (3OQGSGJ GdLOhi hSjGSI GdJhRjY GdCeKd(B- (3JfajP OQGSGJ GdLOhi hbjGS EfJGLjI GdESJKeGQ(B- (3GdOQGSI GdbhejI (B((3OQGSI Jbjje GdQHMjI GdELJeGYjI(B)s
Keywords: (3GdeTQhYGJ(B- (3GdESJKeGQs; (3OQGSI GdLOhis